The Correlation Between Digital Simulation Learning, Basic Programming, Mathematics and Students’ Knowledge: Optimizing Students’ Skill Program for Learning Results - Muhammad Farid; Muhammad Yahya; Dian Atmasani (Journal of Educational Science and Technology (EST), 2021)
The study aims to investigate students learning results of Mathematics, Digital Simulation, and Basic Programming subjects in Vocational High School 7 Takalar and to identify the correlation between students’ learning results on Mathematics and Digital Simulation Subjects and Basic Programming Subject. The research method was ex-post facto. The number of population was 210 and the samples were 63. Data were collected using documentation and test. Hypotheses were tested after performing Prerequisite Test. Results of the study show that: (1) students’ learning results in Mathematics were in the Good category. (2) students’ learning results in Digital Simulation were in the Good category. (3) students’ learning results in Basic Programming were in the Good category. (4) there is a strong correlation between students’ learning results in Mathematics and Basic Programming. (5) there is a strong correlation between students’ learning results in Digital Simulation and Basic Programming, (6) There is a Correlation between students’ learning results on Mathematics and Digital Simulation subjects and Basic Programming subject